Previous radiation for prostate neoplasm alters surgical and oncologic outcomes after rectal cancer surgery. Issue 8 (29th October 2015) - Guandalino, Marlène; Dupré, Aurélien; François, Marie; Leroy, Bertrand; Antomarchi, Olivier; Buc, Emmanuel; Dubois, Anne; Guy, Laurent; Pezet, Denis; Gagnière, Johan
Abstract : Background: Previous radiation for prostate cancer (PC) contra‐indicates neoadjuvant chemoradiotherapy for rectal cancer (RC) because of risk of cumulative radiation dose toxicity. Postoperative outcomes after proctectomy have not been well studied in these patients who did not receive optimal treatment. Methods: Eighty‐four consecutive male patients underwent surgery for stage II–III mid or low RC between 2002 and 2011. Patients who previously received radiation for PC (n = 8) and patients who had not previously undergone radiation for PC but who received neoadjuvant chemoradiotherapy for RC (n = 64) were retrospectively compared. Results: Previous radiation for PC was an independent factor that significantly increased intraoperative (25% vs. 1.6%, P  = 0.002) and postoperative morbidities (62.5% vs. 28.1%, P  = 0.028), anastomotic leakage (62.5% vs. 12.5%, P  < 0.001) and definitive stoma rates (25% vs. 17.4%, P  = 0.022). It significantly altered median overall survival (32.0 vs. 130.6 months, P  = 0.05) and local recurrence‐free survival rates (14.0 months vs. "median not reached, " P  = 0.016). Conclusions: This is the first report of altered survival rates after proctectomy in patients who had previously received radiation for PC. Postoperative morbidity and definitive defunctioning stoma rates were significantly increased in these patients with poor prognoses. Therapeutic strategies should thus be individualized. Large, multicenter cohort studies are needed. J. Surg. Oncol. 2015;112:802–808 . © 2015 Wiley Periodicals, Inc.